NILAI NILAI PENDIDIKAN KARAKTER YANG TERKANDUNG DALAM RAGAM GERAK SENI TARI TENUN BALI (Widyadari : Jurnal Pendidikan, 2021)
Learning dance as an alternative to help introduce and develop students' knowledge about local culture before getting to know outside culture. Education in the modern era now plans character development in every subject. The implementation of character education is that it can be applied to learning dance. The weaving dance depicts Balinese women in making woven fabrics. These character values ​​have a role in shaping a person's character with oneself and others that are contained in their movements. The purpose of this study was to determine the values ​​of character education contained in the weaving dance movement. This research is a qualitative narrative approach. The primary data source was the result of the various motion observations. The analysis technique consists of data reduction and the conclusion of data collection techniques through observation, interviews and documentation. The results show that the tenun dance contains the meaning and values ​​of character education in the presentation of this Tenun Dance movement starting from spinning threads, putting threads on the loom and ending with weaving.